Bridging the Science-Policy Gap – Toward Better Integration of Decision Support Tools in Coastal and Marine Policy Implementation - Schumacher, Johanna; Bergqvist, Lisa; van Beest, Floris M.; Carstensen, Jacob; Gustafsson, Bo; Hasler, Berit; Fleming, Vivi; Nygård, Henrik; Pakalniete, Kristîne; Sokolov, Alexander; Zandersen, Marianne; Schernewski, Gerald (Frontiers in Marine Science, 2020)
Decision support tools (DSTs), like models, GIS-based planning tools and assessment tools, play an important role in incorporating scientific information into decision-making and facilitating policy implementation. In an interdisciplinary Baltic research group, we compiled 43 DSTs developed to support ecosystem-based management of the Baltic Sea and conducted a thorough review. Analysed DSTs cover a wide variety of policy issues (e.g. eutrophication, biodiversity, human uses) and address environmental as well as socio-economic aspects. In this study, we aim to identify gaps between existing DSTs and end-user needs for DSTs for supporting coastal and marine policy implementation, and to provide recommendations for future DST development. In two online surveys, we assess the awareness and use of DSTs in general, as well as policy implementation challenges and DST needs of representatives of public authorities from all Baltic countries, in particular. Through a policy review we identify major policy issues, policies, and general implementation steps and requirements and develop the synthesis-matrix, which is used to compare DST demand and supply. Our results show that DSTs are predominantly used by researchers. End-users from public authorities use DSTs mostly as background information. Major obstacles for DST use are lacking awareness and experiences. DST demand is strongest for the policy issue eutrophication. Furthermore, DSTs that support the development of plans or programmes of measures and assess their impacts and effectiveness are needed. DST supply is low for recently emerging topics, such as non-indigenous species, marine litter, and underwater noise. To overcome existing obstacles, a common database for DSTs available in the Baltic Sea Region is needed. Furthermore, end-users need guidance and training, and cooperation between DST developers and end-users needs to be enhanced to ensure the practical relevance of DSTs for supporting coastal and marine policy implementation. To fill existing gaps, DSTs that address impacts on human welfare and link environmental and socio-economic aspects should be developed. The BSR serves as a best practice case for studying DSTs and their practical use. Hence, our results can provide insights for DST development in other marine regions. Furthermore, our methodological approach is transferable to other areas.